1995
DOI: 10.1006/viro.1995.1218
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Human T-Cell Lymphotropic Virus Type I Expression Following Induction of the Cellular Stress Response

Abstract: Human T-cell lymphotropic virus type I (HTLV-I) infection is typically associated with long incubation periods between virus exposure and disease manifestation. Although viral protein expression is considered to play an important role in the pathogenesis of HTLV-I-associated diseases, limited information is known regarding host cell mechanisms that control viral gene expression. This study was designed to evaluate modulation of HTLV-I gene expression following induction of the cellular stress response in HTLV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…This could indicate that, after stress, there is a shift toward viral production. Indeed, such an effect has been reported in HTLV-1 cells treated with sodium arsenite 59 and in HHV-8-infected primary effusion lymphoma cells treated with arsenic trioxide (G. Torelli, written communication, 2000). These results would also explain why the addition of As 2 O 3 is effective on freshly isolated ATLL cells, which show little, if any, Tax expression but do show NF-B activity.…”
Section: Discussionmentioning
confidence: 90%
“…This could indicate that, after stress, there is a shift toward viral production. Indeed, such an effect has been reported in HTLV-1 cells treated with sodium arsenite 59 and in HHV-8-infected primary effusion lymphoma cells treated with arsenic trioxide (G. Torelli, written communication, 2000). These results would also explain why the addition of As 2 O 3 is effective on freshly isolated ATLL cells, which show little, if any, Tax expression but do show NF-B activity.…”
Section: Discussionmentioning
confidence: 90%
“…Their results demonstrate a clear increase in all proteins associated with the HTLV-1 full-length mRNA, including the polyproteins GagPol (p65) and Gag (p55), as well as the processed protein products p19 and p24 (77). The same report indicates that similar observations are made 24 h after the induction of cellular stress responses (77). This and a subsequent study from the same group (78) conclude that the increase in viral protein expression under cellular stress conditions is regulated mostly at the level of mRNA translation.…”
Section: Discussionmentioning
confidence: 98%
“…Andrews et al (77) showed by Western analysis of proteins extracted from HTLV-1-infected cells that viral proteins are expressed at 48 h after the induction of cellular stress response mechanisms using Na arsenite. Their results demonstrate a clear increase in all proteins associated with the HTLV-1 full-length mRNA, including the polyproteins GagPol (p65) and Gag (p55), as well as the processed protein products p19 and p24 (77). The same report indicates that similar observations are made 24 h after the induction of cellular stress responses (77).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours following electroporation, the expression of hsp 72 was determined by flow cytometric analysis as previously described (5) and the data presented as the percent expression as compared to non-transfected controls. Transfection of HUT 78 cells by electroporation resulted in increased expression (41%) of hsp 72 (as compared to non-transfected, non-stressed controls) (Fig.…”
mentioning
confidence: 99%